(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aimed to discuss and analyze the theoretical framework of sustainability and human capital standards, identify indicators of sustainability standards related to reporting on human capital in the banking sector, and measure the impact of the reflection of the application of sustainability standards in reporting on human capital on the value of Iraqi private banks listed on the Iraq Stock Exchange, as these standards are of great importance in meeting the reporting requirements that serve users of reports in making their decisions. The research sample included (6) banks listed on the Iraq Stock Exchange for a period of (5) years from 2018-2022, and because the indicators for human capital set by the Global Reporting Initiative (GRI) are mostly quantitative indicators because they consist of skills, courses, experiences and capabilities of employees, (Tobin Q) was used to know the value of banks and statistical analysis in order to measure the relationship between research variables and test hypotheses and analyze research results. The research reached a set of conclusions and recommendations, including that there is a direct relationship between the dependent and independent variables, i.e. an increase in the independent variable (implementation of sustainability standards) by one degree leads to an increase of 10.267 in the dependent variable (reporting on human capital), and that there is a direct relationship between the dependent and independent variables, which means that any increase in the independent variable (implementation of sustainability standards) by one degree leads to an increase of 0.697 in the dependent variable (bank value) in light of the intermediate variable (reporting on human capital). It was shown that Iraqi private banks must train their employees periodically and continuously in order to keep pace with developments in the use of information and communications technology, programs and electronic systems, which have become the basis for their work in order to provide the best services to customers. It is important for the Iraqi Stock Exchange and the Central Bank to oblige Iraqi private banks to prepare sustainability reports according to the requirements of sustainability standards.